Effects of Muscle Energy Technique of Upper Trapezius and Sternocleidomastoid Muscles on Bell's Palsy - Jong-Hyeon Park; Yoon-Joo Lee; Hye-Min Ryu; Seung-Jeong Lee; Eun-Jin Park; Choon-Ho Song; Cheol-Hong Kim; Hyun-Min Yoon (MEDrang Inc., 2017)
Background The purpose of this study was to investigate the efficacy of muscle energy techniques (MET) of upper trapezius and sternocleidomastoid muscles on Bell's palsy. Methods In this retrospective study, we screened the medical records of patients with Bell's palsy who had received inpatient and outpatient treatment at the Department of Acupuncture & Moxibustion, Korean Medicine Hospital Dong-Eui University between November 28, 2016 and April 30, 2017. A total of 34 out of 93 Bell's palsy patients met the inclusion criteria. The 34 patients were divided into two groups: Group A patients had undergone Korean-Western combination treatment and MET of upper trapezius and sternocleidomastoid muscles; Group B patients had undergone Korean-Western combination treatment only. MET of upper trapezius and sternocleidomastoid muscles had been performed three times a week during the inpatient period, and two to three times a week during the outpatient period. Yanagihara scores had been assessed at the first visit, and 1, 2, 3, and 4 weeks after the first visit. Results Group A Yanagihara scores were significantly improved during each interval from the first visit to 4 weeks later. Group B Yanagihara scores were also significantly improved except during the first week. During every period, the improvements observed in Yanagihara score were significantly higher in Group A than in Group B. Conclusions These results suggest that MET of upper trapezius and sternocleidomastoid muscles may be effective treatment for Bell's palsy.